Effects of chlorantraniliprole on the life history traits of fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) - Hasnain, Ali; Zhang, Shuirong; Chen, Qinghua; Xia, Lijuan; Wu, Yutong; Gong, Changwei; Liu, Xuemei; Jian, Pu; Zhang, Lei; Wang, Xuegui (Frontiers in Physiology, 2023)
Introduction:Spodoptera frugiperda is an important nomadic agricultural pest with a diverse host range and resistance against several insecticides. The current study investigated the life history traits of two strains of the field-collected population against chlorantraniliprole using an age-stage two-sex life table. Method: For this, we established the chlorantraniliprole-susceptible (Crp-SUS G12), and chlorantraniliprole-reduced susceptible (Crp-RES G12) strains derived from the sixth generation of the QJ-20 population having a resistance ratio (RR) of 10.39-fold, compared with the reported susceptible population. Results: The results showed that the chlorantraniliprole-reduced susceptible strain attained a 4.0-fold RR, while the chlorantraniliprole-susceptible strain attained an RR of 0.85-fold, having overlapped fiducial limits (FLs) with the referred susceptible baseline. Meanwhile, the present study revealed that the development time of the susceptible strain was significantly longer than that of the reduced susceptible strain. Similarly, the mean longevity, adult pre-oviposition period (APOP), and total pre-oviposition period (TPOP) of the female chlorantraniliprole-susceptible strain were considerably longer than those of the female chlorantraniliprole-reduced susceptible strain. Contrarily, the population parameters, including the intrinsic rate of increase (r), finite rate of increase (λ), and net reproductive rate (R), of the chlorantraniliprole-susceptible strain were considerably lower than those of the chlorantraniliprole-reduced susceptible strain, while the mean generation time (T) of the chlorantraniliprole-susceptible strain was substantially longer than the chlorantraniliprole-reduced susceptible strain. The age-stage characteristic survival rate (sxj) and age-stage characteristic life expectancy (exj) of the chlorantraniliprole-susceptible strain were longer than those of the chlorantraniliprole-reduced susceptible strain, but the age-stage-specific reproductive value (vxj) of the chlorantraniliprole-susceptible strain was shorter than that of the chlorantraniliprole-reduced susceptible strain. Moreover, the contents of vitellogenin (Vg) and VgR in the chlorantraniliprole-reduced susceptible strain were higher than those in the chlorantraniliprole-susceptible strain. Discussion: These findings showed that reducing susceptibility to chlorantraniliprole promoted population growth in S. frugiperda. Therefore, this study could provide conceptual support for the integrated pest management (IPM) approach to control S. frugiperda in the field.